Avaliação da saúde mental de puérperas no cenário da pandemia de Covid-19 - Barros, Maria Aline Rodrigues (2023)
This study aimed to evaluate the factors associated with depressive symptoms and fear of Covid-19 in the postpartum period. This is a cross-sectional, quantitative study. The research was carried out in the rooming-in of a University Hospital in Rio Grande, Rio Grande do Sul. The inclusion criteria were women who had recently given birth or had a cesarean section, over 18 years of age in rooming-in. Women who already had a diagnosis of depression, fetal death, premature labor, history of use of antidepressant medications and who had hearing impairment and/or were experiencing a psychotic break were excluded. The sample consisted of 230 women. The data collection period was from March to May 2023. The instruments used were a sociodemographic and obstetric questionnaire, the Covid-19 Fear Scale and the Edinburgh Postpartum Depression Scale. In data analysis, the chi-square test of independence and Fisher's exact test were performed. 200 interviews were collected, the prevalence of postpartum depression symptoms was 19% and the factors that were associated with this condition were: income less than or equal to one salary and not having a partner. Regarding fear of Covid-19, 7.5% of postpartum women were afraid of Covid-19 and the variable that was associated was not having a partner. It is clear that the mental health of postpartum women needs to be better investigated to be diagnosed and treated in a timely manner. Furthermore, it is important that health professionals invest in maternal health care actions throughout the pregnancy and puerperal period, in order to create strategies capable of providing these postpartum women with the support they need in an efficient and humanized way.